Aspects of Veterinary Care and Management of the Philippine Spotted Deer (Cervus Alfredi, Sclater) in Captivity - Alcala, Ely L. (Silliman Journal, 2023)
For the past four years the Silliman University Philippine spotted deer captive breeding facility has successfully pursued its program of breeding Cervus alfredi in captivity. It has adapted a general management procedure similar to that of deer stock farming while at the same time developed basic techniques on various aspects of care and management of the endangered species under captive conditions.